PENGARUH ALAT PERMAINAN SMART CUBE TERHADAP KEMAMPUAN MOTORIK HALUS DAN KEMANDIRIAN ANAK - Fitrianingtyas, Anjar (Institut Daarul Qur'an Jakarta, Indonesia, 2021)
Aspect of motor development as one aspect of development that can be stimulated has an important role in the next stage of a child’s life. The purpose of this study was to analyze the effect of a smart cube on the fine motor skills and independence of children 5-6 years old. The subjects in this study were 20 childrenn 5-6 years old who attended TK Oasis Kids as the experimental group and 20 children 5-6 years old who attended TK PGRI 15 as a control group. The research design used a quasi-experimental study with a pretest-posttest control group design. Data collection techniques used tests, observations, interviews, and documentation. The data analysis technique used T test. The results of this study were that used of the smart cube had an effect on increasing fine motor skills and independence of children 5-6 years old. This evidenced by an increase of 12.65 points in children’s fine motor skills and 16.05 points in children’s independence after being given treatment using smart cube.